PROBLEMS OF SUBJECTIVE PRECONDITIONS FOR THE IMPLEMENTATION OF THE RIGHT TO APPEAL TO COURT (INITIATE A CLAIM) IN CIVIL PROCEEDINGS - Hovhannisyan, Vahe (State and Law, 2025)
In this article, the author has analyzed the issues related to the legality of the exercise of the right to appeal to court by interested persons. As a result of the study of legal literature, case law of the European Court, and the best practices of countries with Anglo-Saxon and Romance and Germanic legal systems, it was found that modern legal regulations on civil procedure, as a rule, provide for mechanisms that exclude the possibility of appeal to court by non-interested persons, which are absent in the legal system of the Republic of Armenia. The author has found that the implementation of the Convention standards for the effective protection of subjective rights and the need for the legitimate exercise of the right to apply to court require the introduction of civil procedural mechanisms and legal remedies in the RA legal system that exclude the examination of claims submitted by non-interested persons, such as the provision in the RA Civil Procedure Code of legal regulations to refuse to accept a claim on this basis and terminate the proceedings, as well as the application of judicial sanctions and the establishment of a disproportionate burden for the distribution of judicial costs.